2021
DOI: 10.1007/s13300-021-01171-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the Glunovo® Continuous Blood Glucose Monitoring System in Chinese Participants with Diabetes: A Multicenter, Self-Controlled Trial

Abstract: Introduction The present study was aimed to evaluate the performance and safety of the Glunovo® real-time continuous glucose monitoring system (CGMS) in monitoring interstitial fluid glucose in adult participants with diabetes (at least 18 years old) using venous blood glucose as control. Methods This was a multicenter, self-controlled clinical trial, conducted in participants with diabetes from China, between March 2019 to October 2019. The CGMS was used by all the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It generates electrical signals, which are transmitted to the mobile application for display of blood glucose readings. While previous studies have indicated the stability and repeatability of Glunovo ® , there remains a lack of head-to-head research to evaluate its accuracy ( 7 ). To address this gap, we conducted a head-to-head study to assess the accuracy of Glunovo ® .…”
Section: Introductionmentioning
confidence: 99%
“…It generates electrical signals, which are transmitted to the mobile application for display of blood glucose readings. While previous studies have indicated the stability and repeatability of Glunovo ® , there remains a lack of head-to-head research to evaluate its accuracy ( 7 ). To address this gap, we conducted a head-to-head study to assess the accuracy of Glunovo ® .…”
Section: Introductionmentioning
confidence: 99%
“…In total, 34 articles identified in the review1 addressed alert evaluation (Supplemental Table), 12-45 and 29 of these reported how alerts were assessed: In 15 of these 29 articles, the alert evaluation was based on individual values, 12-26 6 articles assessed episodes, 27-32 2 articles assessed both episodes and values, 33,34 and 6 seemed to use actually recorded alerts with a value-based approach. 35-40 Especially in the latter case, the language was often not sufficiently clear to make a definitive statement.…”
Section: Assessment Of Threshold Alertsmentioning
confidence: 99%
“…In total, 34 articles identified in the review1 addressed alert evaluation (Supplemental Table), 12-45 and 29 of these reported how alerts were assessed: In 15 of these 29 articles, the alert evaluation was based on individual values, 12-26 6 articles assessed episodes, 27-32 2 articles assessed both episodes and values, 33,34 and 6 seemed to use actually recorded alerts with a value-based approach. 35-40 Especially in the latter case, the language was often not sufficiently clear to make a definitive statement. Notably, there were articles, where the wording “events” was used, while the reported dat...…”
Section: Assessment Of Threshold Alertsmentioning
confidence: 99%
“…Three alternative p‐CGM systems are currently available on the market, each with slightly different technical characteristics (Table S1). 8,9 Of note, the patient is blinded to sensor glucose readings and does not receive any glucose‐related alert or notification while wearing a p‐CGM device, therefore, the HCP can view results that have not been influenced by a patient's decisions in real time 10 . The availability of unbiased glucose data is expected to improve the HCP's understanding of the diverse factors possibly affecting the patient's glycaemic control and guide more appropriate therapeutic intervention, including changes in diet, physical activity (PA), and medications 6 .…”
Section: Introductionmentioning
confidence: 99%